(untitled) (Journal of Economic Research & Business Administration, 2015)
The article is about the internet - trading, about the ways of development of this type of trade in Kazakhstan, on the example of the development of Internet - trading in China. It analyzes the market of Kazakhstan and reflects the perspectives of the development of this type of trade.